Integration and New Limits on Citizenship Rights - Stokes-DuPass, N. author. aut Link
XII, 218 p.
Keywords: Integration and New Limits on Citizenship Rights is a state-centered analysis of citizenship, immigration and social identity. It explores the increasing role of nation states as critical actors in using social policy to affect the social location of immigrants and ethnics and also to redefine what it means to be a full citizen.